Kesiapan Mahasiswa Terhadap Pembelajaran Praktek Pendidikan Teknik Mesin: Survei Pasca Pandemi - Suwondo Hermansah; Sutiman; Farid Mutohhari; Alfat Khaharsyah (Jurnal Pendidikan Indonesia, 2024)
The post-pandemic era of COVID-19 still leaves crucial problems for vocational education (VE), including mechanical engineering education (MEE). Practical learning readiness (PLR), which includes the dimensions of readiness for supporting knowledge, physical and psychological conditions in students, is a fundamental problem that must be solved through systematic mapping. Therefore, this research aims to measure the level of readiness in these three dimensions. In addition, we also examine the differences between dimensions and indicators and test the determination in constructing the PLR to determine systematic problem-solving. The survey was conducted on 386 MEE students, but the final number was 339, considering that 47 of them did not have good data rationale level criteria. The results of the descriptive analysis confirmed that the psychological condition and supporting knowledge had a low level, while the physical condition had a high level. The results of the comparison test show that the three are generally not significantly different, although there are notes in several indicators. Although all dimensions contribute significantly to constructing PLR, psychological conditions contribute the highest. This indicates that low psychological conditions are the first step for VE to suffer. Furthermore, several notes related to the decrease in knowledge-supporting practice are also the second effort that MEE must make in boosting PLR in its students.